Acute cholecystitis during treatment with alemtuzumab in 3 patients with RRMS. (29th November 2016) - Pfeuffer, Steffen; Beuker, Carolin; Ruck, Tobias; Lenze, Frank; Wiendl, Heinz; Melzer, Nico; Meuth, Sven G.
Abstract : Alemtuzumab is an effective therapeutic option for patients with active forms of relapsing-remitting multiple sclerosis (RRMS). 1 The adverse event profile comprises an increased risk for the development of secondary autoimmune disorders as well as infusion-associated reactions. Alemtuzumab infusion is often associated with an acute cytokine release syndrome. 2 Among other side effects, patients may experience headache, rash, pyrexia, and to a lesser extent hypotension, cardiac arrhythmia, and rarely anaphylactic shock. These symptoms are usually limited to the first days of infusion and do not lead to sustained impairment. 1